The use of modern standard and spoken Arabic in mathematics lessons: the case of a diglossic language / El uso del árabe estándar moderno y del árabe hablado en las clases de matemáticas: el caso de una lengua diglósica. Issue 4 (2nd October 2018) - Abbas, Randa; Vaknin-Nusbaum, Vered; Neuman, Ari; Mongillo, Geraldine; Feola, Dorothy; Goldberg Kaplan, Rochelle
Abstract: Researchers have shown an increased interest in the way teachers use their knowledge about language (KAL) to enhance student understanding and learning. This qualitative case study investigated first- and second-grade teachers' use of KAL in Arabic. We investigated the linguistic transitions from standard Arabic to spoken Arabic made by the teachers during mathematics lessons. The results suggested that Arab-speaking mathematics teachers were aware of the gap between home language (Spoken Arabic) and school language (Modern Standard Arabic) and used linguistic transition as a teaching strategy to develop academic thinking and behaviour among their students. The results suggested that Arab teachers built a non-formal bilingual education programme where the two languages were used to teach mathematics. Despite the requirement to use Modern Standard Arabic, participants bridged the gap between the languages, which suggests an inherent understanding that 'language and identity are ultimately inseparable'.